Pd@Pt concave nanocubes with (511) high-index facets for boosting ethanol electrooxidation - Li, Shuhui; Ni, Yujie; Liu, Yutao; Lu, Siyuan; Cheng, Wendan; Zhu, Ting; Ma, Liang (Electrochimica acta, 2025)
•The ultra-small Pd@Pt concave nanocubes (Pd@Pt CNCs) with negative curvature enclosed by (511) high-index facets are successfully synthesized.•The synthesized Pd@Pt CNCs/C with negative curvature shows superior performance in activity, antitoxicity and durability towards the ethanol electrooxidation reaction (EOR), comparing to the Pd@Pt CPs/C catalysts with positive curvature.•DFT calculation reveals that the (511) high-index facets facilitates the dehydrogenation of α-H in ethanol, the generation of -OHads on catalyst surface and the breaking of CC bond for EOR. The ethanol electro-oxidation reaction (EOR) shows slow kinetic and poor CO2 selectivity in direct ethanol fuel cells (DEFCs), which hinders the commercialization of the DEFCs. Shape control and surface structure tuning are not only the general strategies for catalyst performance regulating, but also help us understanding the structure-property relationship in depth. In this work, Pd@Pt concave nanocubes (Pd@Pt CNCs) catalyst enclosed by (511) high-index facets was successfully prepared through seed-mediated growth method. To investigate the influence of curvature on catalysts’ performance, Pd@Pt convex polyhedrons (Pd@Pt CPs) catalyst was also prepared by under-potential deposition (UPD) followed by galvanic replacement for comparison. The Pd@Pt CNCs/C showed enhancements in mass activity, specific activity, antitoxicity and durability toward EOR, comparing to the commercial Pd/C, Pt/C and proprietary Pd@Pt CPs catalysts. The Pd@Pt CNCs/C showed a specific activity of 6.17 mA cm−2, which was nearly 2 times that of Pt/C and Pd/C, and nearly 1.5 times that of Pd@Pt CPs/C. The Pd@Pt CNCs/C catalyst showed superior antitoxicity and durability as well. The peak potential of CO stripping was only 0.68 V, and 57 % of the initial activity remained after 1000 cycles in durability test. Density Functional Theory (DFT) calculation indicated that the (511) high-index facet in Pd@Pt CNCs/C catalyst can effectively promote the dehydrogenation of α-H in ethanol and the generation of -OHads on catalyst surface, and therefore improve the EOR activity. Furthermore, The energy barrier for CC bond breaking had also been decreased, indicating an increase in the selectivity of the CO2 formation. [Display omitted]